A Comprehensive Analysis of Poverty in India - Panagariya, Arvind; Mukim, Megha (MIT Press, 2015)
This paper offers a comprehensive analysis of poverty in India. It shows that regardless of which of the two official poverty lines we use, we see a steady decline in poverty in all states and for all social and religious groups. Accelerated growth between fiscal years 2004–2005 and 2009–2010 also led to an accelerated decline in poverty rates. Moreover, the decline in poverty rates during these years has been sharper for the socially disadvantaged groups relative to upper caste groups so that we now observe a narrowing of the gap in the poverty rates between the two sets of social groups. The paper also provides a discussion of the recent controversies in India regarding the choice of poverty lines.